Multidisciplinary and Comparative Investigations of Potential Psychobiotic Effects of Lactobacillus Strains Isolated From Newborns and Their Impact on Gut Microbiota and Ileal Transcriptome in a Healthy Murine Model - Beck, Bo Ram; Park, Gun-Seok; Jeong, Do Yeun; Lee, Yong Hyun; Im, Sunghoon; Song, Won Ho; Kang, Jihee (Frontiers in Cellular and Infection Microbiology, 2019)
Psychobiotics are probiotic microorganisms that may exert positive influence on the psychological status of the host. Studies have revealed immunological and microbiological correlations of gut microbiota and the gut-brain axis, and have investigated psychobiotics based on the findings of the gut-brain axis. Considering their mode of actions, the present study sets anti-inflammatory effect, neurotransmitter modulation, and gut microbiota modulation as three essential criteria to evaluate Lactobacillus casei ATG-F1 (F1), L. reuteri ATG-F3 (F3), and L. reuteri ATG-F4 (F4) isolated from newborns as psychobiotics candidates in a healthy mouse model and compares the results with a non-treated control group and an ampicillin-induced gut dysbiosis (Amp) group as a negative control. The F3 and F4 strains showed anti-inflammatory effects in vitro in RAW264.7 murine macrophages, and the level of anti-inflammatory cytokine interleukin (IL)-10 increased in ileums of mice orally administered with the F4 strain. Serum dopamine level significantly increased only in the F4-treated group as compared with the control group. Serum serotonin level was unaffected in Lactobacillus-treated groups, while a significant decrease in serum serotonin level was observed in the Amp group. Bacteroidetes population increased in fecal samples of F4-treated group as compared with the control group, and Bacteroidales S24-7 and Prevotellaceae population significantly increased at family level in fecal samples from F4-treated group as compared with the control group. In contrast, the Amp group showed an increase in the level of Proteobacteria and a decrease in the level of Bacteroidetes as compared with the control group. Transcriptome analysis revealed a distinctive clustering in ileums from the F4-treated group as compared to other experimental groups. In addition, the circadian rhythm pathway showed maximum enrichment in ileums of Lactobacillus-treated mice, and the F4-treated group showed the highest fold changes in circadian rhythm-related genes (Dbp, Per1, Per2, and Per3). Conclusively, L. reuteri ATG-F4 is suggested as a potential psychobiotics through demonstrations of anti-inflammatory effects, serum dopamine modulation, and gut microbiota modulation in a healthy murine model in the present study. Moreover, we carefully suggest gut circadian rhythm modulation as another important criterion of psychobiotics, which may have an important role in the gut-brain axis.